The Maturity Level of Operating Informatic Technology to Practice Installation Control and Accredited System (Cobit Ai 5) of Control Objective of Accredited SecurityAnd Operational Testing ( Case Study in PT XYZ Indonesia) - Rima Maulini (Jurnal Ilmiah ESAI, 2011)
Installation processes, testing and receiving system are less formulated even though they were done.  Formation gives big effect to develop informatics technology (IT) which support the use of  IT to reach business aims. The aims of operating AI 5 are:  To do verification and confirm that a solution was relevant to the needed aims through realization of formulated planning about installation, migration, convertion, and acceptance. By using COBIT audit methodology, was well known  the maturity level of operating informatics technology to practice control installation  and accredited system (cobit ai 5) of control objective of accredited security and operational testingfor each controlling item on position 3 ( determined process) and position 4 (can be regulated and measured) Key words: Audit, Cobit, operating